Resenha: VEIGA, Teresa. As enganadas. Rio de Janeiro: 7Letras, 2006, 117 p. (Revista do Centro de Estudos Portugueses, 2008)
Resenha: VEIGA, Teresa. As enganadas. Rio de Janeiro: 7Letras, 2006, 117 p.